Peningkatkan Kemampuan Kognitif dan Minat Belajar Siswa Melalui Penggunaan Alat Peraga Pada Pembelajaran Fisika (UPEJ Unnes Physics Education Journal, 2018)
The purpose of this research is to determine the effect of the use of learning props on the improvement of cognitive abilities and the value of interest in student learning. This research was conducted at SMP Negeri 1 Karangtengah Demak Regency. Cognitive ability was measured using a test instrument in the form of a description test of eight questions, while interest in learning was measured using a questionnaire instrument with a likert scale of 12 statements. The results showed students' cognitive ability increased by 0.51 with the moderate category in all cognitive aspects researched, and students' learning interest showed a very good response on the three aspects researched were 81,12% for pleasure aspects; 83,75% for the attention aspect; and 87,34% for participation aspect. Based on the results of the analysis and discussion, it can be concluded that the use of physics education props can affect the improvement of students' cognitive abilities in grade VIII SMP Negeri 1 Karangtengah Demak Regency. The use of props can also affect the student's interest in learning.